Noodles VR: A 3D Cooking Simulation - Nor Azman, Muhammad Amirul Hariz; Md. Fudzee, Mohd Farhan (Applied Information Technology And Computer Science, 2026)
Southeast Asian noodles, particularly those from Malaysia, Indonesia, and Thailand, have great cultural value. However, traditional learning techniques such as recipe books and videos often fail to attract younger generations, resulting in decreased awareness. Thus, this project aims to design and develop Noodles VR, a virtual reality (VR) application that integrates cooking simulations with cultural storytelling. The target users for this project are young learners and food enthusiasts. The TRES-D methodology was employed in the development process, adopting a user-centered and iterative approach to create an immersive and engaging VR environment. The VR application enables users to interactively learn about food preparation while exploring the cultural significance of each noodle dish. To evaluate the usability of the application, user acceptance testing was conducted using the System Usability Scale (SUS). The average SUS score achieved was 84.38, which falls within the "acceptable" range, receives a grade of B, and is rated as "Excellent" on the adjective rating scale. Overall, the developed application effectively meets the expectations of its target users and contributes to the preservation and appreciation of Southeast Asian culinary traditions through immersive digital learning.